Pendampingan Udar Asumsi dan Membangun Perspektif dalam Upaya Penguatan Moderasi Beragama di Kalangan Cendekiawan Muslim - Effendi, Muhamad Ridwan; Nur Aulia, Rihlah; Narulita, Sari; Mardhiah, Izzatul; Choirur Rizki, Refa; Fahreza, Farhan; Sa’dullah, Sa’dullah (Sivitas : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
Tourism in the Thousand Islands has shown how important it is for the social, economic and cultural life of the local population. However, on the other hand, it has a negative impact on various aspects of community life that are not in accordance or contrary to the social, cultural and religious structure of the community itself. As an educational tourism destination, the Thousand Islands needs mapping and development of various aspects of its tourism, including religious tourism objects. So that the involvement of the Indonesian Ulema Council in this service activity has had a positive impact on the community, this can be seen from the results of the final evaluation of activities in the first year which showed a very good response. However, the success of the program achievements that have been implemented is only through counseling and cannot be seen in the concrete form of the achievement of moderate tourism indicators after the counseling is carried out. So, it is hoped that in the future the target indicators of moderate tourism (non-violence, adaptive to culture, tolerant, and national commitment) can be implemented as expected.